Las condiciones físicas para la práctica del futbol en los deportistas de la selección de fútbol categoría sub 15 de la federación deportiva de los ríos en el año 2016 - Cherrez Vega, Francisco Marcelo (2016)
The work entitled "The physical conditions for the practice of soccer in the sports of football team Category U15 Federation, is a unique and important issue that should be taken into account by the directors of the Sports Federation of Los Rios, can help you eliminate the shortcomings that have their football coaches, with regard to the development of the physical condition of athletes and thus have a positive impact in the direction of physical development of students, research study concluded that debelan the current state of the coaches as well as those aspects that can impartar in the development of these professionals. To achieve the objective methods of theoretical and empirical level of scientific research as well as mathematical and statistical methods were selected. Verification of the hypothesis of planned work was completed by conducting surveys tostudents and coaches as well and basically seven experts consultation, properly selected